(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Karakalpakstan is rich in historical and cultural heritage. The author of the article highlights the problem of familiarizing the schoolchildren to the architectural monuments on the example of the city of Mizdakxana for the purpose of their artistic and aesthetic education. The describe the practice of familiarizing to the monuments of architecture